The relevance of artificial intelligence in Criminal Law: The use of Fuzzy Logic to increase formal social control in the public management of industrial waste (Research, Society and Development, 2024)
The improper disposal of industrial waste generates risks of soil and groundwater contamination, which can trigger significant material and immaterial environmental damage, many of which cannot be reversed. Based on Ordinance No. 280, of June 29, 2020, the Government establishes the control of the transportation and disposal of waste by sending forms by generators and recipients of these materials to environmental control agencies. The use of artificial intelligence (AI) can, from this perspective, be evaluated as a tool to be used in optimizing the management of this information by the public administration, when seeking to identify alert scenarios that may configure, at some point, an environmental crime. This research aims to evaluate the real contribution of the use of artificial intelligence applications, by environmental agencies, to improve the control of the movement and disposal of industrial waste. The methodological approach used was the bibliographic survey and the legislative research. As a result, the significance of the use of artificial intelligence by environmental agencies to reinforce the formal social control of the State was demonstrated, in order to prevent environmental crimes resulting from inappropriate situations involving the movement and disposal of industrial waste.